Impact of Microwave Pre-Curing on Pore Structure and Environmental Performance of Metakaolin- and Fly Ash-Based Geopolymers - Yanhui Dong; Mohamed R. El-Naggar; Runhui Gao; Yefan Li; Yixin Zhao (Buildings)
Microwave technology in geopolymer synthesis offers a transformative, sustainable alternative to traditional methods, enhancing material properties and production efficiency. However, the effects of microwave-induced changes on pore structure and their relationship with mechanical strength and environmental performance, such as heavy metal leachability, are not fully understood. This study investigates the impact of microwave pre-curing on geopolymers, focusing on how microwave power and duration influence their pore structure and environmental performance. A total of 48 mixtures were prepared using sodium silicate and sodium hydroxide as alkali activators, with metakaolin and fly ash as raw materials. The modulus was adjusted to 1.5, and the liquid-to-solid ratio was set at 1.6 for metakaolin and 0.7 for fly ash. Microwave irradiation power settings of 100 W, 300 W, 440 W, 600 W, and 800 W were tested. The heating times ranged from 30 s to 90 s at intervals of 15 s. Our findings reveal that optimal microwave settings (100 watts for 45 s) can significantly enhance mechanical properties, with compressive strengths reaching 15.9 MPa for fly ash-based and 9.094 MPa for metakaolin-based geopolymers. However, excessive microwave energy leads to increased porosity, with adverse effects on structural integrity. Moreover, microwave pre-curing effectively reduces heavy metal leachability. Chromium (III) was used in leaching tests and it was demonstrated that ion concentrations as low as 0.097 mg/L enhance environmental safety. Advanced techniques like Fourier-transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD) and X-ray CT were applied for the analysis of the atomic bonding, phases and pore structure of the studied geopolymers along with their ability to withstand compression (MPa). Chromium (III) was encapsulated and its leached concentration was measured by ICP-MS to evaluate the performance of the synthesized geopolymers. These results underscore the need for precise control over microwave irradiation parameters to maximize the benefits while mitigating negative impacts. This study provides valuable insights into the controlled use of microwave technology for geopolymer synthesis, recommending optimal irradiation conditions for improved performance and sustainability and advancing sustainable construction materials. The developed geopolymers show promise for applications in construction, waste stabilization, and heavy metal immobilization, contributing to more sustainable and environmentally friendly materials in these industries.